Health infrastructure development and its impact on health security in Ethiopia since the 20th Century: Focus on Gojjam Province - Beyene Chekol Syoum; Gizachew Andargie Tefera (Cogent Arts & Humanities)
In Ethiopia, the primary source of medical knowledge from antiquity to the turn of the 20th century was local medical expertise. The western contemporary medical healthcare services didn’t begin till the first decades of the 20th century. Health infrastructure has an unambiguous effect on increasing health security. The most overlooked topics in Ethiopian history and historiography are healthcare and medical history because of its fixation on issues of politics. Pertinent to this, no research has been conducted on the historical growth of medical institutions and their supporting infrastructures, the equitable allocation of people and material resources, and the rate at which public health security has increased in order to balance public mortality in Gojjam Province. Thus, the purpose of this research is to investigate health infrastructure development and its impact on health security in Ethiopia since the 20th century with special focus on Gojjam Province. The qualitative research approach was employed, because it is a representational design that aids in understanding historical processes and human experiences in a specific historical setting. Primary and secondary data sources obtained through interviewing and document analysis were used for this qualitative analysis. The paper discusses the development of healthcare infrastructure, the types of Care Centers, and health security issues in the period under discussion in Gojjam Province. It is hoped that this research will assist experts of the field, the local community, and policymakers better understand how the institutions, infrastructures, and distribution of health services have evolved and impacted health security in Gojjam.